PRELIMINARY STUDY ON OXYGEN TRANSFER FOR LEACHATE WASTEWATER TREATMENT - Septiariva, Iva Yenis; Suhardono, Sapta; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Directorate of Research and Community Service (DRPM), 2022)
Leachate is one of the results of the waste degradation process that can pollute the environment. Leachate is usually treated by biological processes, including aerobic processes that require sufficient oxygen. Oxygen transfer by aeration process is one way to consider gas transfer coefficient (KLa). This study aims to determine the gas KLa kinetics in leachate. This study used a chemical oxygen demand (COD) concentration limit of 100 mg/L. The oxygen flow rates used in this study were 1 L/minute and 1.5 L/minute. The main parameter measured in this study is dissolved oxygen (DO) which is measured by a DO meter every minute. The final DO in this study can be as high as 4 to 6 mg/L. The KLa values in this study show values at the flow of 1 and 1.5 L/min, respectively 0.0095/min and 0.017/min. These results also show that the detention time required for 1 and 1.5 L/min flow rates is 1.75 hours and 0.96 hours. This indicates that the greater the flow rate is given to the oxygen transfer process, the greater the flow rate the KLa value will increase. This will also affect the volume required for the oxygen transfer process. In addition, further research is needed with more diverse variations to further determine the appropriate detention time in leachate processing.